Responses of a bird assemblage to manual shrub removal in a Chacoan subtropical semiarid forest, Argentina - Codesido, M. (2009)
We compared several attributes of vegetation structure of the understory and of bird species richness, guild abundance, and total abundance between a 200-ha area of semiarid Chacoan forest and another 200-ha area of the same forest where shrubs were manually removed, in Santiago del Estero province, Argentina. We seasonally recorded birds at 60 point count stations (30 in each type of habitat) between March 1998 and August 1999. The shrubless area showed higher percentages of herb cover and bare ground than the forest, whereas in the forest there were higher covers of litter and shrubs and a higher shrub height than in the shrubless area. Moreover, the shrubless area showed a lower species richness and bird abundance than the forest in summer. At the guild level, analyses revealed that bark insectivores were more abundant in the shrubless area, whereas foliage insectivores, terrestrial insectivores, and arboreal seed eaters were more abundant in the forest. Our results show that shrub removal has a great influence on the structure of bird assemblages, which persists several years later after the application of this technique. We recommend that, in case of massive shrub removal, stripes of shrubby vegetation should be maintained in order to guarantee the inclusion of shrub-associated bird species in the mosaic landscape. © The Neotropical Ornithological Society.